ANALISIS PSIKOSOSIAL NARAPIDANA PADA KONFLIK ANTAR NARAPIDANA DI LAPAS KELAS IIB SIBORONGBORONG - Jhonson Panahatan Siagian; Wido Cepaka Warih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Prisoners in correctional institutions are still often involved in conflicts, both conflicts between fellow prisoners and between prisoners and officers. These conflicts can occur due to psychosocial problems. Psychosocial problems of prisoners can be caused by the individual (thoughts, emotions and behavior) themselves and from the surrounding environment. The purpose of this study was to see how the psychosocial of prisoners affects the occurrence of conflicts between prisoners in Class IIB Siborongborong Prison and to see what the impacts of the conflicts are. The theory used is Erik Erikson's Psychosocial Theory. This research method is qualitative descriptive with primary and secondary data sources collected through interviews, observations and documentation. Data analysis was carried out through data collection, data reduction, data presentation and drawing conclusions. The results of this study are that the conflicts between prisoners that occurred in Class IIB Siborongborong Prison were influenced by various complex psychosocial and social factors, uncontrolled prisoner emotions, the importance of prisoner awareness to comply with the rules in the prison, and the importance of providing education on psychosocial aspects and emotional management in prison. The psychosocial impact of prisoners greatly contributes to the occurrence of conflicts in prison. Personality changes, such as emotional reactivity, decreased social skills, and aggressive tendencies, create conditions that trigger conflict between prisoners. Conflicts between prisoners that occur can cause disturbances in security and order in prisons. The obstacles experienced are the absence of psychologists in Siborongborong Prison to monitor the mental health and psychological well-being of prisoners, as well as the lack of psychological approaches, namely therapy and counseling to help prisoners overcome their emotional and behavioral problems.